(untitled) (Gaceta Técnica, 2021)
At the age of 70, the architects Jacques Herzog and Pierre De Meuron, founding partners of the Herzog & De Meuron office in 1978, are still leading transformative projects worldwide; their work is recognized for technological innovation in the use of new materials and construction systems. Among his works that draw the most attention are the Dominus Wineries in California in the United States, and the Burgos Railway Boulevard in Spain, inaugurated in 1998 and 2008 respectively. This work is carried out within the framework of celebrating the life of these architects and describing these two great works, which make them distinctive for the level of their designs and construction